PENGEMBANGAN MULTIMEDIA CARD STUDY (CASTU) PADA PEMBELAJARAN LITERASI SAINS UNTUK SISWA KELAS V SEKOLAH DASAR - Nur Afifah, Siti; Siti Raihan; Syamsuddin, Afdhal Fatawuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Limited use of media makes students constrained in developing science literacy. The goal of this research is determine the feasibility of multimedia castu in science literacy learning for grade V elementary school students. The type of research used is Research and Development (R and D) by adopting the Alessi and Trollip development model which consists of three stages, namely planning, design, and development. The research instruments used were in the form of instrument validation sheets, teacher response questionnaires, and student response questionnaires. The sample in this study is grade V students of SD 15 Teddaopu. The results of this research is show that the media developed in science literacy learning has been considered feasible through alpha tests and beta tests. In the alpha validator test, material experts gave an assessment of 96.36% (very feasible) and media experts gave an assessment of 81.8% (very feasible). As for the beta test, the results were obtained based on teacher respondents with a score of 96.15% with the category of product feasibility (very feasible) and students 97.7% (very feasible). Based on the results of the research, it can be concluded that multimedia castu is suitable for use because it is able to present science literacy information visually and interactively